2021
DOI: 10.21608/ejhc.2021.172815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Critical Thinking and Problem Solving Skills on Academic Achievement among Nursing Students'

Abstract: Background: Nowadays all higher educational institutions should develop and enhance their student's critical thinking and problem solving skills to be sure that its products meet or exceed market requirements. this study aimed to determine the impact of critical thinking and problem solving skills on academic achievement among nursing students, Setting; Faculty of Nursing Sohag University The subjects: No. = (448) students all 1 st and 4 th years, they examined using critical thinking, problem solving question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At the end of both semesters, students completed a self-designed survey questionnaire containing 10 items. Responses from the first (25) and second (21) semesters were evaluated separately. The findings revealed that most of the students felt that participating in concept mapping improved their understanding of diet therapy principles (19 of 25; 18 of 21), self-directed learning (14 of 25; 18 of 21), critical thinking (21 of 25; 14 of 21), problem-solving (22 of 25; 16 of 21), and collaboration (24 of 25; 20 of 21) skills.…”
Section: Concept Mappingmentioning
confidence: 99%
“…At the end of both semesters, students completed a self-designed survey questionnaire containing 10 items. Responses from the first (25) and second (21) semesters were evaluated separately. The findings revealed that most of the students felt that participating in concept mapping improved their understanding of diet therapy principles (19 of 25; 18 of 21), self-directed learning (14 of 25; 18 of 21), critical thinking (21 of 25; 14 of 21), problem-solving (22 of 25; 16 of 21), and collaboration (24 of 25; 20 of 21) skills.…”
Section: Concept Mappingmentioning
confidence: 99%